(untitled) (Sciences & Technologie. C, Biotechnologies, 2007)
The optimization of the acidifying power as well as the growth kinetics of Bifidobacterium bifidum, a strain of Streptococcus thermophilus has been associated with it in milk adapted for first age. The antagonistic effect in vitro appears after 4 hours of fermentation, in the presence of B. bifidum in a mixed culture with S. thermophilus. The inhibition percentage of Escherichia coli is 90 %. A decrease of E. coli number is observed after eight hours of fermentation in the presence B. bifidum alone. A great mortality of 50 % is noticed in the mice which have been given only E. coli (set 1). The antagonistic effect in vivo during prophylactic treatment is significantly more important in the presence of two associated species (set 3) than in the case B. bifidum is given alone (set 2). In sets 4 and 5 (therapeutically treatment), a 89.5 % decrease in E. coli in faeces has been noticed during the 2nd day after a dose of fermented milk by B. bifidum in a mixed culture (set 5); but this effect is observed after the fifth when B. bifidum is given alone (set 4). The counts bacterial in the intestinal flora after the dissection of the mice show that B. bifidum and S. thermophilus are situated in the guts of the mice.